(untitled) (Herald of Journalism, 2024)
This article examines the role of authorial subjectivity in the work of Azilkhan Nurshaykov, a writer-journalist who contributed significantly to Kazakhstani literature and journalism. The scientific aspect of A. Nurshaykov’s journalistic activity, which had a large impact on public opinion and played an essential role in the development of humanistic concepts, is discussed. The study’s goal is to describe the author’s concept in journalistic works based on personal experience, perspectives, feelings, analysis and evaluation. The primary focus of the research is the author’s publicistic works, which contain the author’s thoughts and opinions. The author’s perspectives and approaches to public and societal issues are taken into account in the journalist’s profession. The author’s notion will be acknowledged in philosophical, social, cultural, personal, and other aspects depending on the work’s subject and genre. The study examines theoretical and empirical methodologies, as well as contextually analyzing essential characteristics of authorship that contribute to the integrity and uniqueness of a journalist’s work and determine individual style. This helps readers comprehend the concept of authorship in a journalist’s work. The paper investigates the journalistic laboratory he worked in for nearly two decades and analyzes his perspectives on the concept of journalist. A writer-journalist’s viewpoint based on life experience is critical for developing journalists’ professionalism and competency. The study’s relevance and innovation stem from the development of contextual analyses that connect the author’s subjectivity in journalism with the stylistic-genre, creative, and poetic characteristics of A. Nurshaykov’s works. The article’s value is additionally boosted by providing theoretical explanations of features of authorial subjectivity of international and domestic journalists, including the role of journalistic texts in content production and their influence on reader perception.